Planar Microcavity-enhanced Lasing from Semiconducting Carbon Nanotubes - Yang, HeeBong (University of Waterloo, 2025)
Single-walled carbon nanotubes (SWCNTs) exhibit exceptional optical properties, including strong oscillator strength, size- and chirality-dependent tunable bandgap energies, and near-infrared (NIR) photoluminescence (PL) at room temperature. These features make them highly attractive and promising candidates for a wide range of optoelectronic and quantum optical applications. However, their practical deployment has been significantly hindered by several challenges such as PL quenching due to nanotube bundling, structural degradation from high-temperature annealing, or internal loss mechanism of exciton-exciton annihilation (EEA) under high excitation power. To overcome these challenges and enhance the radiative efficiency of SWCNTs, we design and fabricate wafer-scale dielectric distributed Bragg reflectors (DBR) to construct high-quality Fabry-Perot (FP) planar microcavities, where thin films of chirality-sorted, well-dispersed SWCNTs. These cavities serve to promote strong light-matter coupling between confined cavity photons and excitons in the SWCNT films. We perform optical characterization of the SWCNT-embedded microcavity devices both in weak and strong light-matter coupling regimes. First, in the strong coupling regime, we observe the SWCNT exciton-polariton dispersions with vacuum Rabi splitting (VRS) strength around 210 meV. Unfortunately, the polariton condensation was not achieved, primarily due to internal material loss mechanisms such as EEA process or strong reabsorption. On the other hand, we observe nonlinear lasing behavior in weak light-matter coupling regime, evidenced by a pronounced spectral linewidth narrowing signature with increasing excitation power. This would represent the first demonstration of lasing from SWCNT thin films integrated into planar dielectric microcavities, marking a significant milestone in carbon-based nanophotonics. While the results are promising, there remains considerable scope for enhancing the coherence and quality of the emitting light from these SWCNT-embedded microcavity devices, an essential step toward realizing scalable quantum nanophotonic platforms.